The physics of solar cells : perovskites, organics, andphotovoltaic fundamentals - Bisquert, Juan (Boca Raton, FL : CRC Press, Taylor & Francis Group, 2018)
'Energy devices with solar cells and batteries are crucial in the drive to obtain a carbon-free energy economy. Funding and commercial applications are focused on developing new materials and devices that perform required energy conversion and storage processes with high efficiency, adequate capabilities, and low production costs. This book provides an accessible summary and introduction of the main physicochemical principles that govern solar cells, perovskites, and organic materials. Recent rapid advances in the science and technology of solar cells with the discovery of perovskite solar cells and their development to a highly efficient semiconductor solar cell are highlighted'--cProvided by publisher
Blackbody radiation and light -- Light absorption, carrier recombination and luminescence -- Optical transitions in organic and inorganic semiconductors -- Fundamental model of a solar cell -- Recombination current in the semiconductor diode -- Radiative equilibrium in a semiconductor -- Reciprocity relationships and the photovoltage -- Basic operation of solar cells -- Charge separation in solar cells -- Charge collection in solar cells -- Solar energy conversion concepts
Keywords: Photovoltaic cells; Solar cells